WASTE MATERIAL SEGREGATION USING ATMEGA - Sana, Nabila; *, Renu; Rajan, Ritu; Maheshwari, Bhavya; Kumar, Akshay (IJRDO - Journal of Electrical And Electronics Engineering, 2017)
The aim of this project is to successfully design, build, and test a system that identifies and segregates recyclable waste materials like glass, plastic, metal, paper and wood into their proper bins. .The growing population of India poses serious huge problem with regard to the availability of living space. But another serious or rather a huge problem that follows is the rapidly increasing amount of waste generated each minute or each second by an individual. Sadly, only 5% of this total amount of waste is recycled. One possible solution for this problem could be segregating the waste at the disposal level itself. In India, the collection, transportation and disposal of material segregation waste are unscientific and uncontrolled. Uncontrolled dumping of waste on outskirts of rural and urban areas has created serious environmental implication or problem in terms of ground water pollution and contribution to Global warming .This has found adverse effect to reduce the average life span of the manual segregators. Developing a mechanized system that helps to save the lives of many human beings and making the world a cleaner and a greener place is the noble objective of our project. We have thus proposed an waste material segregator that aims at segregating the waste at the disposal level itself. It is designed to sort the waste into 4 major categories, namely metallic, colour, wet and dry, thereby making waste management more effective. To set the ball rolling, we have proposed this project to give back to our nation, making our India a “Swachh Bharath”.The Swachh Bharat project was proposed by our honourable Prime Minister MR. Narendra Modi.